PERJANJIAN TIDAK TERTULIS DITINJAU DALAM SUDUT PANDANG HUKUM PERDATA - Ayu Puspita, Berliana Adinda; Marwiyah, Marwiyah (MAGISTRA Law Review, 2024)
The existence of unwritten agreements is also based on the principle of freedom of contract, which gives parties the freedom to determine the type of agreement they will make. Traditional societies often use unwritten agreements in business transactions. In most cases, agreements between two parties are made in writing, with the rights and obligations of the parties clearly written down. If the agreement is not made in writing, or better known as an "oral agreement", it will be difficult for the parties to prove it if a breach of contract occurs. An agreement that has valid legal force based on an agreement between the parties involved and is made orally without being documented in writing is called an unwritten agreement. Unwritten agreements are weaker than written agreements, especially in cases of disputes. The purpose of this writing is to analyze the existence of unwritten agreements in civil law. The methodology used is a normative research method used with an approach to written legal rules. The results of the discussion show that if an oral agreement meets the legal requirements according to the formulation of Article 1320 of the Civil Code, then the agreement is valid and has legal force to declare someone in default. However, if the verbal agreement is denied or not acknowledged by the party suspected of being in default, the agreement does not have legal force to declare someone in default. This is because the agreement can be true and fulfill the legal requirements of the agreement.